2022
DOI: 10.3390/fermentation8070330
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antihypertensive Effect of Fermented Sargassum horneri with Lactiplantibacillus pentosus SN001

Abstract: Sargassum horneri is a seaweed with antihypertensive properties. However, it is underutilized in some areas, and effective utilization methods are being sought. In this study, we prepared a fermented S. horneri using lactic acid bacteria Lactiplantibacillus pentosus SN001 and investigated its effective utilization by enhancing its antihypertensive effect. The ACE inhibitory activity of S. horneri ranged from 3.6% to a maximum of 63.3% after fermentation. In vivo studies using mice and spontaneously hypertensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For example, the biomass of Sargassum horneri (a seaweed with antihypertensive properties) showed an enhancement of this biological activity after lactic acid fermentation by Lactiplantibacillus pentosus bacteria. It was found that glycerol was responsible for the antihypertensive action in this case [98] .…”
Section: Lactic Acid Fermentationmentioning
confidence: 55%
“…For example, the biomass of Sargassum horneri (a seaweed with antihypertensive properties) showed an enhancement of this biological activity after lactic acid fermentation by Lactiplantibacillus pentosus bacteria. It was found that glycerol was responsible for the antihypertensive action in this case [98] .…”
Section: Lactic Acid Fermentationmentioning
confidence: 55%
“…Among probiotics, strains from the Lactobacillaceae and Bifidobacteriaceae families are involved in fermentation; they regulate microbial growth and the enzymatic conversion of food constituents 6 , 7 , which in turn produces beneficial end-products, such as organic acids, bacteriocins, and peptides 8 . In a previous report, S. horneri fermentation with Lactiplantibacillus pentosus SN001 increased glycerol levels, in which elevated antihypertensive effects 9 . Therefore, fermentation is a prominent tool for enhancing the value of biomaterials.…”
Section: Introductionmentioning
confidence: 74%
“…S. horneri water extracts and fermented products of those were prepared 44 . S. horneri was washed, dried at 50 °C for 24 h, and ground.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To activate L. plantarum 002, which had been stored at −80 °C, it was inoculated into ILS (International Lactobacillus Subcommittee) medium according to previous studies (Sekine et al ., 2022; Tamura et al ., 2022) and pre‐cultured (30 °C, 24 h). To 100 mL of 33 mM phosphate buffer solution (pH 5.0), 5 g of Hidakakombu powder was added and stirred.…”
Section: Methodsmentioning
confidence: 99%